Beyond Boundaries : New York's New Art - Saltz, Jerry; Smith, Roberta (New York : Alfred Van der Marck Editions, 1986)
Periodically, the art world is rocked by explosions - by the emergence of new artists, new genres, new forms and images, new values and concerns. The art surveyed in Beyond Boundaries is now generating shock waves that are being felt worldwide. Although few if any new Superstars have yet arisen, there is little doubt that many will appear - and equally little doubt that most of those are included in this book. Not only new, but also radical in their techniques, these artists combine painting, sculpture, and photography in a stylistic diversity that ranges from hyperrealism to geometric abstraction. The art speaks with many faces and many voices, yet is united by its time and place and by its explosive development as a significant force in contemporary art. As Roberta Smith writes in her introductory essay : This is no longer a time of polar (or semipolar) oppositions.... The territories opened during the past fifteen years are now being scutinized in detail.... Under negotation is a new, more completely balanced art.... In addition, there seems to be a pervasive realization that pleasrure is its own form of knowledge, that few things communicate like an engaging visuality. The pleasures of the text are not incompatible with those of the object. By presenting a partial census of some of the best and most promising art in New York in the mid 1980s, we hope to demonstrate something important about both the recent past and the immediate future.
Beckman, Ericka ; Belcher, Alan ; Bender, Gretchen ; Bickerton, Ashley ; Birnbaum, Dara ; Bleckner, Ross ; Casebere, James ; Charlesworth, Sarah ; Clegg & Guttmann ; Condo, George ; Dunham, Carroll ; Dwyer, Nancy ; Ess, Barbara ; Fischer, R.M. ; Fujita, Kenji ; Gober, Robert ; Goldin, Nan ; Goldstein, Jack ; Halley, Peter ; Hansell, Freya ; Innerst, Mark ; Joelson, Suzanne ; Kass, Deborah ; Kessler, Jon ; Knight, Karla ; Minter, Marilyn ; Kohlhöfer, Christof ; Koons, Jeff ; Kruger, Barbara ; Larmon, Kevin ; Lasker, Jonathan ; Lawler, Louise ; Lemieux, Annette ; Levine, Sherrie ; McCollum, Allan ; McDermott & McGough ; Mentor, Will ; Nadin, Peter ; Nagy, Peter ; Newman, John ; Otterson, Joel ; Prince, Richard ; Rockman, Alexis ; K.O.S. ; Rollins, Tim ; Schuyff, Peter ; Simmons, Laurie ; Steinbach, Haim ; Stephan, Gary ; Storey, David ; Taaffe, Philip ; Tansey, Mark ; Vaisman, Meyer ; Wallace & Donohue ; Westfall, Stephen ; Winters, Terry ; Wool, Christopher
biog. en tekst per kunstenaar p. 123-128
Engels
boek
Keywords: New York; Amerika; Verenigde Staten van Amerika